Mechanical performance improvement of super absorbent polymer-modified concrete - Dilbas, Hasan; Birdal, Furkan; Parim, Co Kun; Gunes, Mehmet amil (ELSEVIER, 2023)
In this study, a method has been developed to reduce the negative effects of superabsorbent poly-mers on concrete mechanical properties. The method involves concrete mixing and curing, with the concrete mixture being designed using a decision tree algorithm. Instead of the standard wa-ter curing approach, air curing conditions were used during the curing process. In addition, heat treatment was applied to reduce any possible negative effects of the polymers on the concrete's mechanical properties and to enhance their performance. The details of all these stages are pre-sented in this method. Various experimental studies were conducted to demonstrate the validity of this method, which proved to be effective in reducing the negative effects of superabsorbent polymers on concrete mechanical properties.center dot The method can be used to eliminate the negative effects of superabsorbent polymers.center dot The proposed method yielded promising results, demonstrating that the expected level of compressive strength, modulus of elasticity and toughness in concrete can be achieved in 5-10 days instead of 28 days center dot The widespread use of superabsorbent polymers in the concrete industry and reinforced con-crete systems can be attributed to their many benefits.
Keywords: Concrete with super absorbent polymer; Curing conditions; Heat treatment; Stress-strain relationship; Modulus of elasticity; Toughness; Science & Technology - Other Topics